2021
DOI: 10.1109/access.2020.3048193
|View full text |Cite
|
Sign up to set email alerts
|

Peak to Average Power Ratio Based Signal Detection for Frequency Shift Multitone SWIPT System

Abstract: In this paper, we investigate a multitone simultaneous wireless information and power transfer (SWIPT) based modulation scheme for battery-less Internet of Things (IoT) nodes that works in the ultra high frequency (UHF) region. The conventional SWIPT system is assumed to have power-consuming communication modules. Having such modules on to the IoT nodes whose power is harvested from radio frequency (RF) power sources is too unrealistic. In addition, waveform design from the aspect of power harvesting through S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…6(a). Using the Fourier transform pair y env (f ) of the envelope signal in (11), the frequency-domain expression of the input signal at the FS PAPR estimator is given by…”
Section: B Unified Receiver With Papr Modulation: How It Workmentioning
confidence: 99%
See 2 more Smart Citations
“…6(a). Using the Fourier transform pair y env (f ) of the envelope signal in (11), the frequency-domain expression of the input signal at the FS PAPR estimator is given by…”
Section: B Unified Receiver With Papr Modulation: How It Workmentioning
confidence: 99%
“…Meanwhile, it was shown that the RF to direct current (RFto-DC) power conversion efficiency (PCE) in EH circuits of SWIPT receivers depends not only on the input power but also the shape of the input signal, i.e., peak-to-average power ratio (PAPR), due to the nonlinearity of the rectifier, such as diode small signal [5], [6] and saturation effect [7]. Following this observation, new modulation schemes which utilize multi-tone waveforms for boosting the PCE were proposed in [8]- [11]. The authors in [8] proposed the PAPR modulation for SWIPT using distinct levels of signal PAPR to convey information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize these ripples, a multitone frequency shift keying (FSK) scheme is introduced, where the tones' frequency spacings are varied according to the transmitted information, and information decoding is performed by Fast Fourier Transform (FFT) [27]. Another way of decoding information from multitone FSK is considering the fact that multitones with different frequency spacings result in different PAPR levels, which further helps in reducing the receiver power consumption by the removal of FFT [28]. A way of utilizing the phase of 2-tone signal is introduced in [25].…”
Section: Introductionmentioning
confidence: 99%
“…13). Further, decoding at the receiver can be performed in two ways: either by using Fast Fourier Transform (FFT) for identifying the strongest baseband signal, or by evaluating multitone PAPR levels with the changing frequency spacings to lower the power consumption at the receiver [59]. In this way, a 0.55 V output voltage can be attained, which is higher than the amplitude based biased-ASK waveform.…”
mentioning
confidence: 99%